The influence of debt policy on firm value with firm size as a moderating variable. - I Pande Putu Suwisnaya; Komang Ayu Krisnadewi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this study is to provide empirical evidence about the effect of debt policy on the company’s value where the size of the company as a moderating variable. This study was performed on companies listed in Indonesia Stock Exchange in 2012-2015. The total sample of 88 companies with a total number of observations as much as 352 observations. The analysis technique used is the moderated regression analysis (MRA). The company's value in this study is proxied by the price book value (PBV), while the debt policy is proxied by debt to equity ratio (DER), and the size of the company is proxied by the natural logarithm of total assets. Based on the analysis found that the debt policy significant positive effect on the value of the company, which weakens the relationship between the size of the company's debt policy on the value of the company.